Strength Development of Epoxy Grouts for Pipeline Rehabilitation - Lim, Kar Sing; Siti Nur Afifah, Azraai; Nordin, Yahaya; Zardasti, Libriati; Norhazilan, Md Noor (Penerbit Universiti Teknologi Malaysia, 2017)
Polymeric composites are increasingly being used as infill material in civil engineering applications for repairing damaged structures, including corroded pipelines. In repairing damaged pipelines, combination of composite layer and infill materials is a preferable technique used in oil and gas industry. It is desirable for a repair work to be completed in a short period of time. More importantly, as the repair work is done, the structure is expected to back in service soonest possible to minimize the financial loss due to production interference. This paper investigates the development of tensile and compressive strength of two epoxy grouts over 28 days. This research program aims to improve fundamental understanding of this material and its potential application in repairing damaged pipeline. A total of 80 samples with different curing times were prepared based on manufacturer’s guideline. The samples were then cured in room temperature for 1, 7, 21 and 28 days before tested using universal testing machine. The trend of strength development over time was studied to identify the time at which the grout can be considered capable of serving in service condition. It was found that the compressive and tensile strength of both grouts greater than 70MPa and 14MPa at 1days curing time, respectively. The strength is about 80% developed for 1-day curing time. When comparing the properties of the tested grouts with previous studies, both grouts were found to have the potential to be used as infill material for repairing damaged pipeline. In addition, for application of compressive strength and tensile strength less than 70MPa and 14MPa, both grouts can be considered as capable to serve its repair purpose after the grout cured for 1 day.